UPAYA PERANAN GURU PKN DALAM MENGATASI MASALAH PENYEBARAN BERITA HOAKS DI MEDIA SOSIAL PADA SISWA SMP NEGERI 1 TELLU SIATTINGE - Astuti, Rena; Yanis, Muhammad; Genda, Maming (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the increasing spread of false information among students, which has become a serious concern, particularly due to low digital literacy skills and students’ limited awareness in verifying the accuracy of received information. Civic Education (PKn) teachers have the responsibility not only to teach citizenship knowledge but also to shape students’ character so they can think critically, act wisely, and behave responsibly in responding to digital information flows. This research employed a qualitative approach using a descriptive method. Data collection techniques included observation, interviews with PKn teachers and the Student Council President (OSIS Chairperson) as student representatives, and documentation. The findings indicate that PKn teachers play a strategic role as educators, mentors, and facilitators in developing students’ awareness of the dangers of hoax news. The results show that the role of PKn teachers is highly important in preventing the spread of hoax information within the school environment. Support from all parties, including schools and parents, is necessary so that efforts to improve digital literacy can be implemented more optimally and sustainably.